The Effectiveness of Medical Record Software to Improve Administrative Service Ability and Student Motivation - Mokhamad Firman Ismana; Iis Iis; Abas Hidayat (UIN Sunan Gunung Djati Bandung, 2023)
Technology can improve the learning process more quickly and effectively to improve students' cognitive skills. Technology-based learning media is not only for prospective teachers but can be helpful for prospective health workers. One indicator that shows prospective health workers' quality is the health services' ability. Therefore, preparing prospective health worker students who are technologically literate and highly motivated is necessary. This study aims to determine and analyze the effectiveness of Medical Information System software to improve the ability of health administration services and student motivation. The quantitative method with pre-experimental design. Pre-experimental design with one group through pre-test, intervention (treatment), and post-test. This research was conducted at STIKes Cirebon with a total sample of 110 students. The results showed that after implementing the medical record software, descriptively, there was an increase in the percentages of responsiveness, reliability, assurance, empathy, and administrative service quality. In addition, each indicator of student motivation increases. Based on hypothesis testing, it can be concluded that Medical Information System medical record software can significantly improve the ability of health administration services and student motivation. This research contributes to providing information to students and lecturers about health administration learning technology.